Effects of Injectable Propofol Emulsion on Singlet Oxygen Released From Activated Human Neutrophils and That Chemically Generated - Chika Senda; Yoko Nishinaka; Toshiyuki Arai; Hajime Segawa; Hiroko Mori; Mitsuru Nonogawa; Nobuyuki Endo; Takashi Miyoshi; Kouhei Yamashita; Masataka Sasada (Elsevier, 2008)
Effects of an injectable emulsion of propofol and its emulsifier on singlet oxygen (1O2) were examined. 1O2 released from activated human neutrophils was detected by chemiluminescence, and chemically generated 1O2 was detected by electron paramagnetic resonance (EPR). Both the propofol emulsion and the emulsifier suppressed 1O2 release from neutrophils. However, the emulsifier did not quench chemically generated 1O2, while the propofol emulsion quenched it. These results indicated that the emulsifier did not scavenge 1O2 released from neutrophils but inhibited 1O2 generation. The suppressive effects of propofol emulsion on 1O2 release from neutrophils consist of 1O2 scavenging and inhibition of 1O2 generation. Keywords:: propofol emulsion, emulsifier, singlet oxygen